Theories of informetrics and scholarly communication : a festschrift in honor of Blaise Cronin - Sugimoto, Cassidy R.; Cronin, Blaise (De Gruyter, 2016)
Scientometrics have become an essential element in the practice and evaluation of science and research, including both the evaluation of individuals and national assessment exercises. This book brings together the theories that guide informetrics and scholarly communication research. It is a timely and much needed compilation by leading scholars in the field, and covers all aspects that guide our understanding of authorship, citing, and impact.